Controlling for survey costs when estimating covariances between Pathak estimators in fixed-budget sequential sampling - Szymoniak-Książek Krzysztof; Gamrot Wojciech (Journal of Economics and Management)
Aim/purpose – This work aims to assess stochastic properties of finite population mean estimators under Pathak’s fixed-cost sequential sampling scheme by deriving their covariance and proposing its estimator. This scheme enables strict control over survey-related monetary expenditures when individual data acquisition costs differ and survey budget excesses are unacceptable. It facilitates economically efficient use of available resources. Our work is aimed at extending its applicability.